Rainfall/runoff modeling of Taman Mayang sub catchment / Mohamad Suhaini Nordin - Nordin, Mohamad Suhaini (1996)
This study is to determine the runoff coefficient for overland flow in an urbanization catchment are, a relationship between rainfall intensity. Taman Mayang catchment area in Petaling Jaya has been selected as a study case.